From war to peace on the Mozambique-Malawi borderland - Englund, Harri (Edinburgh : Edinburgh University Press for the International African Institute, 2002)
This is a full-length ethnography telling villagers' stories from war to peace in Mozambique. Extended case studies of villages and families on the Mozambique-Malawi borderland form the core of this study.
Includes bibliographical references (pages 196-211) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Ethnology -- Mozambique; Ethnology -- Malawi; Mozambique -- Social conditions -- 1975-; Malawi -- Social conditions -- 20th century; War and society -- Mozambique; War and society -- Malawi; Ethnologie -- Mozambique; Ethnologie -- Malawi; Mozambique -- Conditions sociales -- 1975-; Malawi -- Conditions sociales -- 20e siècle.; Guerre et société -- Mozambique; Guerre et société -- Malawi; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; Ethnology; Social conditions; War and society; Malawi; Mozambique; Grensgebieden; Oorlogsslachtoffers; Casestudies; Since 1900